(3MRH GdfhQs - (3Ydj Hf YHO Gddg GdTGPdj, fhQ GdOjf CHj GdMSf,J (B656 (3g` s
(3ChdgG (B:s
(3jGddg jG fhQ jG Mb jGeHjf GaJM bdHi HfhQc hYdefi ef Ydec hagefi Yfc hGSeYfi efc s
(3BNQgG (B:s
(3Cf JLYdfi HGdCShI GdMSfI GdJi cGfJ ai EHQGgje hGdPjf eYg EP bGdhG dbhege EfG HQGA efce heeG JYHOhf ef Ohf Gddg caQfG Hce hHOG HjffG hHjfce GdYOGhI hGdHZVGA CHOkG MJi JhefhG HGddg hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeSs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B662s
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9321) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs